Investigation on the distribution status of microalbuminuria population in Qingdao area - LIANG Mei; XUMei; LIU Chang-jiang; RAO Xiao-pang (Linchuang shenzangbing zazhi)
Objective To investigate the distribution status of microalbuminuria in abnormalities population of different metabolic and understand the contribution of different risk factors on microalbuminuria.Methods In 2012,Chengyang District People’s Hospital of Qingdao city participated in the epidemiological survey of chronic diseases(4 650 cases),1 170 cases were randomly selected as the subjects of this study,urinary albumin and Urinary creatinine were randomly determined in the early morning,albumin creatine rate urinary(UACR) was calculated to evaluate the micro albumin urine index.and according to the level of UACR,those were divided into:Normal albumin urine group(NAU,male 398 cases,female 409 cases) and microalbuminuria group(MAU group,male 175 cases,female188 cases),the study subjects were collected the clinical data and biochemical indexes,statistical analysis uses SPSS16.0 software.Results(1)Compared with the NAU group,the MAUgroup,age,FBG,DBP,SBP,SUA,WC,WRS),WHR was higher than that of the NAU group,the difference was statistically significant(P<0.05 or P<0.01);compared with the NAU group,high blood glucose,hypertension,dyslipidemia and obesity especially abdominal obesity prevalence rate of the NAU Group increased,the difference was statistically significant(P<0.05 or P<0.01);(2)Crosstable analysis results showed that urine albumin,high blood sugar,high blood pressure,simple obesity rates were 24.9%,17.2%,10.2%,hyperglycemia and hypertension or urine albumin obesity rates were38.7%,29.3%,hypertension and obesity trace albumin urine detection rate was 22.1%,Metabolic syndrome,urine albumin the rate was 43%,the risk was 3.75,2.74,2.10,5.26,4.34,3.86 and12.3;(3)Logistic regression analysis DBP,WC,WSR,WHR,FBG were the risk factors of microalbuminuria,The risk of FBG is the greatest,followed by high DBP,and high WSR and high WC,and finally,the high WHR.The OR values were 6 386,4.65,3.32,2.08 and 1.87.Conclasions The main risk population of MAU in Qingdao area was HG,followed by the PHT population,and also for the OB population,especially the AOB population,The more risk factors clustered,the higher the risk of MAU.